2009
DOI: 10.1177/009164710903700301
|View full text |Cite
|
Sign up to set email alerts
|

The ABC-X Model of Family Stress in the Book of Philippians

Abstract: Throughout history, families have dealt with stress and crises. Hill's 1949 ABC-X model of family stress remains a useful tool for identifying the different components that affect how successfully families cope with stress. Paul's letter to the Philippians expands and illustrates this model. Therapists working with Christian families and individuals can use this model and Paul's epistle as a structure to help identify the type of stressor being experienced, explore family resources, and evaluate the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…This was particularly evident with regard to effective communication, which basically should have enabled them to coordinate resources and efforts to cope with the demands the critical events have placed on the family. Namely, we found that the communication patterns in place tended to exacerbate the situation through disagreement, yelling and harsh words against each other (Wilmoth and Smyser, 2009). Perry and his son Charles were particularly very impulsive during the family workshop, yelling at each other and disagreeing on JFBM strategic decisions of the family business (e.g.…”
Section: Initial Situationmentioning
confidence: 90%
See 2 more Smart Citations
“…This was particularly evident with regard to effective communication, which basically should have enabled them to coordinate resources and efforts to cope with the demands the critical events have placed on the family. Namely, we found that the communication patterns in place tended to exacerbate the situation through disagreement, yelling and harsh words against each other (Wilmoth and Smyser, 2009). Perry and his son Charles were particularly very impulsive during the family workshop, yelling at each other and disagreeing on JFBM strategic decisions of the family business (e.g.…”
Section: Initial Situationmentioning
confidence: 90%
“…The Double ABC-X Model not only focuses on the interplay of internal and external influencing factors but also highlights the relevance of prior experiences in dealing with challenges. The second part of the diagram shows the post-crisis phase, during which problem solving and coping are at the center of the post-crisis stage (Wilmoth and Smyser, 2009). Several dimensions are important to define the family's adaptation to the new situation, and these include adaptive resources (such as family hardiness and social support), pile-up of demands and perception (such as coherence among the family).…”
Section: Resilient Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Family Stress (Wilmoth, 2009) define family stress as a condition where environmental demands exceed the individual or collective family resources, disrupting the family system. Also, (Sunarti, 2012) uses the term pressure to describe the stress felt by the family and defines it as the family's perception of the problems it feels, which based on its source, can be divided into three components, namely: economic pressure, psychological pressure, and social pressure.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…How families respond to a stressful event, namely their coping strategies were studied mainly in the case of normative stressful events (Daneshpour, 2017;González & Lorenzo, 2012;Janis, Callahan, Shelton, & Aubuchon-Endsley, 2016;Wilmoth & Smyser, 2009). This includes, for instance, families where there are members with chronic illnesses (Coppetti et al, 2019;Nabors et al, 2018;Park & Choi, 2017;Rolland, 2000;Schaffiner, 2014), autism (Krakovich, McGrew, Yu, & Ruble, 2016), elderly abuse perpetrated by informal caregivers (Lee, 2009), and those with disabilities (Ricketts, 2020).…”
Section: Introductionmentioning
confidence: 99%